An Exploratory Study of Remote Offshore Employee’s Engagement: A Study on North Sea Offshore Remote Workforce - Beena, Manjusree (Global journal of Business and Integral Security, 2023)
The UK North Sea is known as the Oil capital of Europe and plays a significant role in the country's economy, providing 49% of offshore employment. However, the industry has faced challenges in recent years due to economic downturns and the COVID-19 pandemic. These difficulties have resulted in strained relationships between employers and employees, low engagement levels, and a high turnover rate. This paper is attempted to explore employee engagement among the offshore remote workforce of the North Sea's Oil and Gas industry and provide organizations with a framework for improvement. Employee engagement is crucial for organizational success, fostering a positive atmosphere and encouraging committed, energetic employees who contribute to overall success. The study uses both qualitative and quantitative approaches, including interviews and a questionnaire survey. The findings suggest that current strategies for driving employee engagement in the offshore industry need revision, emphasizing the importance of establishing trust and fostering a positive relationship between employees and organizations. The outcome from the research study can be used to provide an overview and references on some of the practical work undertaken in the area of the employee engagement practices in the North Sea's Oil and Gas industry. Keywords: Employee Engagement, Offshore, Psychological Contract, Leadership.